Theorizing race and cultural autonomy in education: An extension of differentiation and integration in Paul Willis's Learning to Labour. (December 2018) - Dinsmore, Brooke
This paper addresses a misreading of Willis's Learning to Labour within the American sociology of education, arguing that his central theoretical move, the treatment of cultural production as autonomous from social reproduction, has been neglected. Willis's concepts of differentiation and integration extend dominant cultural approaches to racial inequality in education, theorizing how youth's oppositional countercultures emerge through conflict with the institutional logic of schools. However, Willis's theorization must be extended to account for race in addition to class and gender. Using black working-class boys in American schools as a comparison case, this paper argues that race alters the temporality of differentiation, with black boys perceived as noncompliant and disruptive by teachers prior to participating in high school oppositional countercultures. In response, black boys develop strategies of integration, managing their cultural performances to re-establish the terms of the educational exchange. These strategies may help facilitate class mobility for black youth.